From Catch to Consumer: A Process-Centric Model for Resilient Fisheries Value Chains - M Arif Kamal; Aunur Rofiq Mulyarto; Usman Effendi (Journal of Information System and Informatics, 2026)
Capture fisheries value chains are highly fragmented and time-sensitive, with multiple stakeholders and perishable products creating persistent challenges for quality management, traceability, and resilience. Many improvement initiatives prioritize digital technologies, yet benefits often remain limited when tools are not embedded in day-to-day business processes. This study proposes a process-centric framework that integrates Porter’s Value Chain with Business Process Model and Notation (BPMN) to diagnose and redesign capture fisheries workflows. Using a case-based approach, As-Is BPMN models are developed across key actors—fishing vessels, landing/auction sites, processors, and distributors—to identify process gaps, information discontinuities, and subjective decision points that weaken end-to-end traceability and quality assurance. Building on these insights, a To-Be process architecture is designed that embeds standardized identifiers, explicit decision logic, quality checkpoints, and traceability controls directly into operational workflows. The findings indicate that process-oriented redesign strengthens information continuity, accountability, and compliance readiness, shifting traceability from a retrospective reporting obligation to an operational management mechanism. Methodologically, the study demonstrates how Porter’s Value Chain can function as a process landscape and how BPMN connects strategic value creation to execution. Practically, the framework offers actionable guidance to improve governance and resilience in capture fisheries value chains.